1989
DOI: 10.1111/j.1748-1716.1989.tb08760.x
|View full text |Cite
|
Sign up to set email alerts
|

The cold pressor test: effects on sympathetic nerve activity in human muscle and skin nerve fascicles

Abstract: Micro-electrode multi-unit recordings of muscle nerve sympathetic activity (MSA) involved in cardiovascular homeostasis or skin nerve sympathetic activity (SSA) involved in thermoregulation were made in the right peroneal nerve of 48 healthy volunteers during performance of the cold pressor test, i.e. immersion of one hand in ice water (2 +/- 0.5 degrees C) for 1 min. Eleven subjects underwent the same procedure on a second MSA recording occasion. As a rule, immersion evoked an increase in MSA, with a gradual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
124
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 25 publications
5
124
0
Order By: Relevance
“…Usually, the cardiovascular response to the CPT includes a slight increase in heart rate (Victor et al, 1987;Fagius et al, 1989), which has not been observed in the present experiment of localized hand cooling. However, it has been suggested that the acceleration of heart rate is related to the pain sensation which is induced by the immersion of the whole hand in ice water (Victor et al, 1987).…”
Section: Localized Cooling Of the Skinmentioning
confidence: 60%
See 4 more Smart Citations
“…Usually, the cardiovascular response to the CPT includes a slight increase in heart rate (Victor et al, 1987;Fagius et al, 1989), which has not been observed in the present experiment of localized hand cooling. However, it has been suggested that the acceleration of heart rate is related to the pain sensation which is induced by the immersion of the whole hand in ice water (Victor et al, 1987).…”
Section: Localized Cooling Of the Skinmentioning
confidence: 60%
“…The increase in MSNA and blood pressure during hand cooling is a well known effect and this response has been used as CPT in several studies as a standardized baroreflex-independent stimulatory manoeuvre of the MSNA (Victor et al, 1987;Fagius et al, 1989). The parallel increase in blood pressure and MSNA during the CPT has led to the conclusion that a change of the baroreflex inhibitory level was induced by some extraordinary input operating during the manoeuvre (Fagius et al, 1989).…”
Section: Localized Cooling Of the Skinmentioning
confidence: 99%
See 3 more Smart Citations